Climate Change-Induced Disaster and Its Impact on the National Security of Nepal - Kapri, Chandra Shekhar (Unity Journal, 2024)
In the 21st century, Climate Change emerges as a non-traditional but significant contemporary challenge, acting as a potential threat multiplier in the realm of non-conventional security. While this change poses a major global environmental challenge, particularly affecting Asia, a few studies argue the ramifications of climate change for national security. As a Himalayan country, Nepal, being unique topographically with an altitude ranging from 60m to 8848.86m, is prone to various kinds of disasters, including climate change-induced among many. Existing scholarship on national security, few have explored the potential threats due to its impacts, however, the domestic literature lacks clarity on Nepal’s vulnerability towards this. In this context, geographically located in the lap of the Himalayas, Nepal has been lagging far behind in grasping the issue of climate change through the lens of national security. This study maps the possible connection between these two by examining the major adverse environmental trends and disasters that pose a security threat to Nepal. It also aims to explore the ways to potential mitigating or adaptation measures to the effects of climate change on national security which eventually helps security professionals, scholars, and decision-makers. This article uses a content analysis approach to conclude the collected information where thematic analytical interpretation is used.